Analisis Pemahaman Kebijakan Hukum Terhadap Bullying dalam Pendidikan di Sekolah Menengah Pertama - Hikmah, Nur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the understanding of legal policies on bullying in education in junior high schools. This research is an analysis of the study of policies that regulate bullying. The type of research used is qualitative descriptive based on research sources and the development of experts and legal experts. All data collected is data derived from the results of expert analysis that is developed and adapted to the current situation. The data analysis process used is qualitative data analysis with the stages of data reduction, data presentation, and conclusion drawing. The results of data analysis show that children's development without strong monitoring and assistance will result in children easily falling or being affected by self-motivation without any boundaries that they understand and fear. Children in the immature category without sufficient experience will be able to feel okay by committing bullying behavior. The lack of understanding of students and children towards the provisions and policies of the law that regulates bullying makes children or students feel uncontrolled in committing bullying or as a victim of bullying